How Menstruation Is Perceived by Adolescent School Girls in Gedeo Zone of Ethiopia? - Zelalem Belayneh; Moges Mareg; Birhanie Mekuriaw (Obstetrics and Gynecology International)
Introduction. Perception regarding menstruation is insufficiently acknowledged. Lack of adequate perception towards menstruation may make girls vulnerable to mental, emotional, and physical problems. This might also be a reason for the failure of menstrual hygiene practice which in turn can have multiple social and health consequences. Objective. To assess the perception and correlation regarding menstruation among adolescent high school girls in Gedeo zone, Southern Ethiopia. Methods. An institutional-based cross-sectional study was conducted among a randomly selected 791 adolescent high school girls at the Gedeo zone through the multistage sampling technique. Data were collected using an interviewer-administered questionnaire. The data were entered to EPi Info version 3.5 and exported to SPSS version 20.0 for analysis. Frequency tables were used to describe study variables. Odds ratio with 95% confidence interval was computed to determine the level of significance. Result. From a total of 806 adolescent girls that were invited to participate in the study, 791 (98.1%) participated. The mean (±SD) age of respondents was 16.3 (±4.7) years. Living alone in dormitories {OR = 1.75 CI = (1.07, 2.85)}, lower maternal educational status {OR = 4.03, CI = (2.41, 6.74)}, and age of menarche before 12 years {OR = 2.07, CI = (1.02, 4.24)} were factors statistically associated with unfavorable perception regarding menstruation. Conclusion. Most high school girls had an unfavorable perception regarding menstruation. Living alone, lower maternal educational status, and age of menarche before 12 years were factors with statistically significant association with unfavorable perception regarding menstruation. This demonstrates a need to design and implement advocacy programs.